SETTLEMENT OF INTERNATIONAL DISPUTES PEACEFULLY BASED ON INTERNATIONAL LAW PRINCIPLES - Widya Setiabudi Sumadinata (Fox Justi : Jurnal Ilmu Hukum, 2023)
Prevention of the use of violence or the occurrence of war between countries is absolutely necessary to avoid violations of international law and security. In international relations between countries, harmony is needed in various activities, and this will not be achieved if the parties do not have good faith in resolving their disputes. International law regulates the dispute in the United Nations Charter. Therefore the purpose of this research is to analyze the peaceful settlement of international disputes based on the principles of international law. This research uses a qualitative approach with descriptive methods. The results of the study show that international disputes can occur due to poverty and injustice, racial and religious differences, extremism, controversy and discrimination. In the settlement of international disputes peacefully can be done in three ways, namely through diplomatic channels, legal channels, and through international organizations.